Pentingnya Komunikasi Kepala Sekolah Dengan Guru Dalam Menciptakan Lingkungan Sekolah Positif - I Putu Risky Ardana Putra; Ayu Karnadi, Kadek; Bisma Taruna Dalem, Kadek; Wira Ananta Sesana, I Made; Helin Dwi Sartika, Kadek; Redan Werang , Basillius (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
Effective communication between principals and teachers plays an important role in creating a positive school environment. This study aims to examine the role of principal communication at SDN 5 Busungbiu in building harmonious relationships with teachers, supporting the teaching and learning process, and improving the overall quality of the school environment. This study uses a qualitative approach with a descriptive method, involving in-depth interviews, observations, and document analysis as data collection techniques. The results of this study are expected to provide an overview of the communication strategies implemented by principals, the obstacles faced in the communication process, and their effects on teacher work motivation, team collaboration, and student engagement. In addition, this study will also explore how effective communication can help create an inclusive school culture, support innovation, and strengthen relationships between all school stakeholders. This study has a significant contribution in offering practical recommendations for principals and other educational leaders to improve the quality of their communication, thereby creating a conducive school environment, supporting teacher professional growth, and having a positive impact on student academic achievement.